2014
DOI: 10.1177/0003489414538606
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Hearing Outcomes by Multiple Regression Analysis in Patients With Idiopathic Sudden Sensorineural Hearing Loss

Abstract: Prediction of HLpost by the multiple regression model may be useful to estimate the hearing prognosis of ISSNHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…Although predicting the prognosis in advance is of primary interest to SSHL patients and physicians, very few studies have covered this theme and they usually involved traditional models based on regression methods or Bayesian survival analysis. Those studies did not focus on the prediction of dichotomised hearing outcome, but rather on prediction of the time to improvement with the best ROC‐AUC of 0.807 or hearing improvement rate with the highest predicable probability of 70%, thus disabling direct comparison with our study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although predicting the prognosis in advance is of primary interest to SSHL patients and physicians, very few studies have covered this theme and they usually involved traditional models based on regression methods or Bayesian survival analysis. Those studies did not focus on the prediction of dichotomised hearing outcome, but rather on prediction of the time to improvement with the best ROC‐AUC of 0.807 or hearing improvement rate with the highest predicable probability of 70%, thus disabling direct comparison with our study.…”
Section: Discussionmentioning
confidence: 93%
“…Suzuki H et al developed a regression model with four predictors including initial hearing threshold, age, the presence of vertigo and time from onset to treatment, achieving predicable probability of 70% but a wide prediction interval (40 dB) and low multiple correlation coefficient (0.495). Recently they improved the multiple correlation coefficient (0.714) for their predictive model by adding three more predictors (contralateral hearing level, initial hearing level at low frequencies and at high frequencies) . Chao TK and Chen T established a Bayesian cure rate model by inputting eight variables, predicting the time to improvement in idiopathic SSHL patients, with the area under the receiver operator characteristic curves (ROC‐AUC) at the 7th, 14th and 30th days were 0.709, 0.752 and 0.807, respectively …”
Section: Introductionmentioning
confidence: 99%
“…8 In earlier literature, older age in treated ISSNHL patients tends to be associated with a worse prognosis [12][13][14][15] or no change in hearing improvement. [16][17][18] One prospective, longitudinal cohort study of 127 ISSNHL patients found no significant difference in PTA recovery rates in the various age groups studied (30, 31-50, 51-70, 71 years old), but did note a trend in poorer results in the more extreme age groups (30, 71 years old) 19 Attanasio et al 20 found increased age was associated with worse hearing outcomes in their study of 496 patients; on subgroup analysis divided by age >65 years old, patients in the older subgroup had a statistically significant higher PTA both pre-and posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…The association between the subjective perception of vertigo and worse outcome could be demonstrated by several studies [32, 33, 3645]. But, the association between objective calorimetric tests and hearing outcome was only investigated by a few [29, 31, 32].…”
Section: Discussionmentioning
confidence: 99%